Secondary school mathematics and entrance into the STEM professions: a longitudinal study - Ortal Nitzan-Tamar; Zehavit Kohen (SpringerOpen, 2022)
Abstract Background STEM (Science, Technology, Engineering, and Mathematics) fields are in high demand for qualified personnel worldwide, yet drop-out rates of a career path in STEM occur at various points in lifespan. Based on a big-data analysis of 534,590 records retrieved from the Israeli Central Bureau of Statistics for several points in time over one and a half decades, the study aims to examine the various pathways of which secondary school students take toward STEM-related careers, and to characterize each pathway based on various demographic and educational factors. Results The study presents a three-tier tree, which highlights eight pathways leading to STEM or non-STEM bachelor's degrees. An important finding is the recognition of a non-linear pathway, demonstrating the biggest 'leak' from STEM in secondary school to non-STEM in higher education. Further, findings indicate that choosing advanced mathematics, majoring in physics and computer science in secondary school, and excelling in mathematics or science major at secondary school, have a lasting effect on STEM persistence in higher education. Additionally, males and non-minorities populations have the highest likelihood of choosing STEM for future studies. Conclusions The study contributes theoretically to broadening the conceptualization of various pathways toward pursuing a STEM career across important choice stages in people's lifespan. Moreover, the study provides insight into the long-term effect of education choices made in secondary school, as well as demographic and educational factors, on future choice for study.